Pengaruh Kualitas Makanan Dan Kewajaran Harga Terhadap Kepuasan Pelanggan Dengan Citra Merek Sebagai Variabel Mediasi: Studi Pada Pelanggan Produk Snack Kentang French Fries 2000 Di Kota Semarang - Renata Renata; Idris Idris (Diponegoro Journal of Management, 2026)
This study aims to analyze the effect of food quality, price fairness, and brand image on customer satisfaction with French Fries 2000 products in Semarang City. This study is based on the phenomenon of the sales performance gap between PT Siantar Top products and its main competitors in digital market. In addition, brand image is tested as a mediating variable to clarify the mechanism of consumer satisfaction formation. The research methos used was quantitative, with questionnaires distributed to 106 respondents through purposive sampling. The research population consisted of French Fries 2000 consumers in Semarang City who were at least 17 years old. Data analysis was performed using the Partial Least Squares Structural Equation Modeling (PLS-SEM) approach with SmartPLS software. The results showed that food quality, price fairness, and brand image had a positive and significant effect on customer satisfaction, both directly and indirectly. Brand image was found to be the most dominant predictor in determining customer satisfaction with a path coefficient of 0,539. These findings confirm that a strong and thrustworthy brand reputation is a key factor for PT Siantar Top in maintaining consumer satisfaction amid competition in the food industry.